A THREE LAYER SUPPLY CHAIN COORDINATION POLICIES FOR PRICE SENSITIVE AND EXPONENTIALLY DECLINING DEMAND WITH RECOMMENDED RETAIL PRICE BY MANUFACTURER - Nigwal, A. R.; Khedlekar, U. K.; Chandel, R. P. S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
The article develops an integrated supply chain coordination for multi-channel and multi-echelon supply, in which a single manufacturer, multiple non-competitive distributors, and non-competitive retailers are work together as members of the supply chain. The formulation of this model is based on deterministic exponential decreasing and price-dependent demand on the retailer's end. We formulated the model in two different scenarios, first, one is decentralized,d and the second one is centralized. The integrated profit function has been derived for each supply chain member, incorporating sharing holding costs among the distributors and retailers. We optimized selling price, economical order quantity, wholesale price, and profits for every echelon supply chain member in the finite and certain time horizon for decentralized and centralized scenarios respectively. Finally, we have done sensitivity analysis for some key parameters to examine their influence on the model's outputs. On the basis of numerical studies, we have also proposed managerial insights.